Medical equipment management: a case study from Wiyung Sejahtera Hospital in Surabaya, Indonesia - Puspitasari, Sendhi Tristanti; Kurniawan, Roni; Ambarsari, Ayu (2017)
The effective maintenance management of medical technology influence the quality of care delivered and the profitability of healthcare fasilities. A good management in technology maintenance must be done, so medical equipment can be used timely, safet and approriate by operational standard for diagnostic. This study aimed to explore medical equipment management in Wiyung Sejahtera Hospital. A case study was conducted in Wiyung Sejahtera Hospital during two months (August until September in 2016). Collecting data through indept interview and observation in healthcare unit which using medical equipment. Assessment of the medical equipment management based on WHO guidelines about technology management cycle for healthcare. This study showed that bad medical equipment management make financial loss. Medical equipment management included planning and assessment, budgeting and financing, technology assessment and selection, procurement and logistics, installation and commissioning, training and skill development, operation and safety, maintenance and repair, decomissioning and disposal. Additionally, a medical equipment maintenance optimization module and quality control system are incorporated. The system is, therefore, expected to improve the realibility of medical equipment and significantly improve safety and cost-effeciency.